Object Properties Influence Visual Guidance of Motor Actions - Scrafton, Sharon (Vision (Basel), 2019)
The dynamic nature of the real world poses challenges for predicting where best to allocate gaze during object interactions. The same object may require different visual guidance depending on its current or upcoming state. Here, we explore how object properties (the material and shape of objects) and object state (whether it is full of liquid, or to be set down in a crowded location) influence visual supervision while setting objects down, which is an element of object interaction that has been relatively neglected in the literature. In a liquid pouring task, we asked participants to move empty glasses to a filling station; to leave them empty, half fill, or completely fill them with water; and then move them again to a tray. During the first putdown (when the glasses were all empty), visual guidance was determined only by the type of glass being set down—with more unwieldy champagne flutes being more likely to be guided than other types of glasses. However, when the glasses were then filled, glass type no longer mattered, with the material and fill level predicting whether the glasses were set down with visual supervision: full, glass material containers were more likely to be guided than empty, plastic ones. The key finding from this research is that the visual system responds flexibly to dynamic changes in object properties, likely based on predictions of risk associated with setting-down the object unsupervised by vision. The factors that govern these mechanisms can vary within the same object as it changes state.